Development of Interactive Video-Based Mathematics Learning Media to Improve Senior High School Students' Conceptual Understanding - Salman Alfarisi; Fatus Atho’ul Malik (Indonesian, 2023)
Students’ poor understanding of mathematical concepts remains a persistent problem in education, particularly at the high school level. One contributing factor is the limited variety of instructional media capable of visualizing abstract concepts in a concrete way. This study aims to develop an interactive video-based mathematics learning medium that is valid, practical, and effective in improving high school students’ conceptual understanding. The study employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The test subjects were 11th-grade students at MA Ibadurrochman in Malang. Data collection instruments included validation sheets from subject matter experts and media experts, a student response questionnaire, and a concept comprehension test. The results showed that the interactive video learning media developed received a validation score of 87.5% from subject matter experts and 85.2% from media experts, both falling into the “highly suitable” category. Student responses to the media reached 84.6%, falling into the “very good” category. The results of the effectiveness test howed an increase in students’ conceptual understanding with an N-Gain value of 0.62 in the moderate category. The conclusion of this study is that interactive video-based instructional media is suitable and effective for use as a medium for teaching mathematics in high school.